Electric field–induced strain behavior and ferroelectric properties of lead zirconate titanate-barium calcium zirconate titanate ceramics. Issue 187 (12th February 2018) - Butnoi, P.; Manotham, S.; Jaita, P.; Sweatman, D.; Pisitpipathsin, N.; Tunkasiri, T.
ABSTRACT: In this work, electric field-induced strain behavior and ferroelectric properties of x BCZT/PZT (with x = 0, 4 and 8 mol%) ceramics have been investigated. The Ec and Pr increased with increasing electric field and exhibited pinched-shape hysteresis loop at 60 kV/cm. The abnormal domain walls and switching behavior of the domains were used to discuss the above results. The strain value increased with increasing BCZT content and reached the maximum value of 0.27% ( d * 33 = 450 pm/V) for the 4 mol% BCZT sample. This offered an opportunity to obtain a good candidate for using in piezoelectric applications.